Development of Sustainable Solvent and Its Thermodynamics Study for Polyolefin Polymer Recycling - Zakaria, Mohamad Hazwan (Universiti Teknologi PETRONAS, 2014)
This project is comprised of development of a sustainable solvent for polymer recycling process. The type of polymer used is waste polymer polyolefin. The procedure that is incorporated for recycling these polymers is called dissolution/ reprecipitation method. This procedure required dissolution of polyolefin in solvent and another non-solvent to reprecipitate the solvent. Solvent use in this study is a mixture of toluene and naphthalene at a certain ratio. Results showed that by using this solvent mixture, it can dissolve more polyolefin polymer at a low temperature. For Low Density Polyethylene (LDPE) and High Density Polyethylene (LDPE), the ratio of waste polymer to solvent is 1:20. For Polypropylene (PP), the ratio of waste polymer to solvent is 1:21. All polymers dissolve at temperature of 90 ⁰C.